2014
DOI: 10.11604/pamj.2014.18.255.3607
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and Education in developing countries: a survey of school teachers’ knowledge about epilepsy and their attitude towards students with epilepsy in Northwestern Nigeria

Abstract: IntroductionStudents living with epilepsy still find themselves confronted with social barriers that prevent them from academic achievements.ObjectiveThe aim of this study was to evaluate knowledge and attitudes of school teachers and to determine the factors associated with good knowledge and positive attitude among nursery, primary and secondary school teachers in Kano, Northwestern Nigeria.MethodsA 20-item validated semi-structured questionnaire was self-administered to 200 teachers, selected through multis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 27 publications
3
27
2
Order By: Relevance
“…Other studies found similarly unsatisfactory responses concerning first aid measures in children with epilepsy [5,7,15,19,20,22,23]. In undeveloped countries, these percentages were even higher, like a study from Nigeria, according to which over 80% of teachers were not familiar with first aid management of a seizing child [8]. In Montenegro, paramedics are always called by school staff in any case of emergency, especially seizures.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Other studies found similarly unsatisfactory responses concerning first aid measures in children with epilepsy [5,7,15,19,20,22,23]. In undeveloped countries, these percentages were even higher, like a study from Nigeria, according to which over 80% of teachers were not familiar with first aid management of a seizing child [8]. In Montenegro, paramedics are always called by school staff in any case of emergency, especially seizures.…”
Section: Discussionmentioning
confidence: 95%
“…Most questions were designed as a choice from "yes, " "no, " or "not familiar with the disease, " while questions regarding etiology of epilepsy, clinical manifestations of an attack, and first aid management permitted multiple answers. The questions were derived from the questionnaires used in previous studies that quantified the knowledge, attitudes, and practice towards epilepsy among selected populations [7][8][9][10]. The questionnaire was translated into Montenegrin from the English version and went through translation and back-translation.…”
Section: Methodsmentioning
confidence: 99%
“…The knowledge score was further categorized as poor (0–5), fair (6–10), or good (11–15). The attitude score was categorized as negative (0–5) or positive (6–10) [21, 2426]. …”
Section: Methodsmentioning
confidence: 99%
“…Although, several studies have reported high level of awareness in various population, the reported misconceptions, religious and cultural beliefs about the cause and management of epilepsy and stigma experience of people with epilepsy have made the life of these people miserable indicating urgent need to address these research findings [15][16][17]. Community-based education is reportedly very useful in correcting these ignorance, misconceptions, negative religious and cultural beliefs about the disease [18,19]. Health workers with targeted training about such disease will be able to carry out this community health education among community members that include opinion leaders (traditional rulers, religious leaders), the youth or the elderly [20,21].…”
Section: Introductionmentioning
confidence: 99%